Pain as a risk factor for substance use: a qualitative study of people who use drugs in British Columbia, Canada - Pauline Voon; Alissa M. Greer; Ashraf Amlani; Cheri Newman; Charlene Burmeister; Jane A. Buxton (BMC, 2018)
Abstract Background People who use drugs have a significantly higher prevalence of chronic non-cancer pain compared to the general population, yet little is known about how various policy, economic, physical, and social environments may serve as risk or protective factors in the context of concurrent pain and substance use. Therefore, this study sought to explore perspectives, risks, and harms associated with pain among people who use drugs. Methods Thirteen focus group interviews were held across British Columbia, Canada, from July to September 2015. In total, 83 people who had lived experience with substance use participated in the study. Using an interpretive description approach, themes were conceptualized according to the Rhodes' Risk Environment and patient-centered care frameworks. Results Participants described how their experiences with inadequately managed pain in various policy, economic, physical, and social environments reinforced marginalization, such as restrictive policies, economic vulnerability, lack of access to socio-physical support systems, stigma from health professionals, and denial of pain medication leading to risky self-medication. Principles of patient-centered care were often not upheld, from a lack of recognition of patients as experts in understanding their unique pain needs and experiences, to an absence of shared power and decision-making, which often resulted in distrust of the patient-provider relationship. Conclusions Various risk environments and non-patient-centered interactions may contribute to an array of health and social harms in the context of inadequately managed pain among people who use drugs.